PENGARUH CUSTOMER EXPECTATIONS DAN PERCEIVED VALUE TERHADAP CUSTOMER SATISFACTION PADA USER APLIKASI DINOTIS - Kinanthi, Glory Easterlitta; Sisilia, Kristina (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Digital transformation in technology, information and communication is driving innovation in how people interact. Dinotis is a start-up company in the telecommunications and entertainment industry to connect creators and audiences. Dinotis relies heavily on the satisfaction of both creators and audiences to continue contributing and subscribing to their platform. This can be known by understanding the variables of expectations and perceived value of its consumers. So this research aims to find out how customer expectation and perceived value affect customer satisfaction in Dinotis application users. The quantitative research method used is descriptive causal involving 100 respondents who use the Dinotis application. The sampling technique used is non probability sampling with purposive sampling type which is processed using the SPSS 26 application. Based on the results of simultaneous and partial hypothesis testing, customer expectation has no significant effect on customer satisfaction, while perceived value has a significant effect on customer satisfaction. However, simultaneously there is a significant effect of customer expectation and perceived value on customer satisfaction with the Dinotis application.